Adsorption of Methylene Blue using Activated Carbon Made from Watermelon Rinds - Garba, Abdurrahman; Tahir, A.; Abdulazeez Kankia Yusuf (Journal of Sustainable Materials Processing and Management, 2021)
This work reports the possibility of using sustainable waste from watermelon rinds as a potential candidate for the removal of methylene blue (MB) from aqueous solution in batch mode. The adsorbent was characterized by FTIR and SEM where the FTIR analysis shows peaks at 3370 cm-1 that corresponds to –OH stretching vibration for lignin, pectin and cellulose, at 1728 cm-1 corresponds to –C=O stretching of esters, carboxylic acids, and as well peak in the range of 1350 – 1000 cm-1 which indicates stretching vibration of alcohols and carboxylic acids. The availability of hydroxyl and carboxyl groups enhance high MB uptake at lower pH. The SEM image of raw adsorbent shows no development of pores, but after carbonization the pores were developed due to escape of volatile groups during carbonization and activation process. Adsorption studies using batch mode were performed by varying adsorption parameters such as adsorbent dosage, contact time, pH of the solution and initial dye concentration. The maximum capacity of the adsorbent was found to be 0.4g dosage, pH 4, 20mg/L of initial MB concentration and 60 minutes contact time that removes maximum of 197.5 mg g-1. The results indicated that watermelon rind is a successful agricultural waste that could be utilized for sustainable removal of cationic dyes in aqueous solutions.